Physical Activity for Families - Jamie C. Stolarz; Karla P. Shelnutt; Andrea Nikolai; Annie Sheldon Wallau (EDIS)
This publication highlights health benefits and recommendations for physical activity. It also includes tips for being active and suggests fun activities that the whole family can do together. Written by Jamie C. Stolarz, Karla P. Shelnutt, Andrea Nikolai, and Annie Sheldon Wallau, and published by the UF/IFAS Department of Family, Youth and Community Sciences, revised February 2022.